An observational study to analyze predisposing factors, causality, severity and preventability of adverse drug reactions among multidrug resistant tuberculosis patients treated under RNTCP program in Northern India - Lakhani, Preet; Singh, Divya; Barua, Shireen; Jain, Suchi; Kant, Surya; Verma, Ajay; Sachan, Amod K.; Nath, Rajendra; Dixit, Rakesh K. (International Journal of Research in Medical Sciences, 2019)
Background: There were 4.1% of all new cases and 19% of previously treated patients were diagnosed with either multidrug resistant or rifampicin resistant tuberculosis in 2016. In the state of Uttar Pradesh, there were 2.16 new cases and 44,531 previously treated cases. The objectives of the study were to assess the predisposing factors, causality assessment, severity grading and avoidability of the adverse drug reactions (ADRs) of the antitubercular drugs in MDR-TB patients in a tertiary care hospital of northern India. Methods: This prospective observational study was conducted for 12 months at a tertiary care hospital. The patients with MDR tuberculosis on treatment with DOTS Plus regimen under RNTCP and who met the inclusion exclusion criteria were recruited after informed consent. ADRs were monitored daily till the patients remained admitted and thereafter monthly. Predisposing factors were recorded. Causality assessment was performed by Naranjo scale and WHO UMC scale, severity by Hartwig’s scale and avoidability by Halla’s scale. Results: There were 115 patients were recruited, 70 developed at least one ADR. 98 ADRs were reported. The commonest ADR reported were – gastrointestinal (38.76%), neurological (21.24%) and hepatobiliary (8.16%). Diabetes and HIV predisposed to development of ADRs. 58.18% ADRs were classified as possible and 37.5% as probable by Naranjo’s scale. 51.02% ADRs were classified as probable and 42.83% as possible by WHO-UMC. 56% were classified as mild, 36% moderate, and 6% severe via Hartwig’s scale. 51 ADRs were classified as avoidable and 40 ADRs were possibly avoidable. Conclusions: Monitoring and assessment of ADRs is necessary to promote awareness, curb resistance and maintain adherence.